Chronic phospholipase D1 inhibition via small molecule inhibitors ameliorate dendritic spine dystrophy in ADRD mouse models via phosphocofilin mediated changes: Molecular and cell biology/protein‐protein interactions. (7th December 2020) - Natarajan, Chandramouli; Bourne, Krystyn Z.; Medina Perez, Carlos X.; Krishnan, Balaji
Abstract: Background: Phosphatidyl choline phospholipase D (PC‐PLD), a lipolytic enzyme that breaks down membrane phospholipids via two isoforms ‐ a constitutively expressed PLD2 and an inducible PLD1 isoform ‐ are also involved in developmentally important signaling mechanisms that regulate synaptic function. We were the first to propose and present a systematic study that established PLD1 as the aberrantly elevated isoform in AD and related dementia using human clinical samples and provided functional proof using mouse models to demonstrate the underlying synaptic dysfunction and memory deficits. Method: Synaptosomal Western blot analysis on 3xTg‐AD mice hippocampi were used to investigate neuronal PLD1 expression and function. Long term potentiation of PLD1 dependent changes using pharmacological approaches in ex vivo slice preparations from wildtype and transgenic mouse models were used to assess synaptic perturbations that were first studied using the novel object recognition memory (NOR) and fear conditioning (FC) paradigms. Chronic PLD1 small molecule inhibitor treatment was assessed in different age groups to ascertain the efficacy of treatment at different stages of Aβ and tau‐driven AD‐like memory deficit progression in transgenic animal models. Lastly, brain tissues from these animals were subjected to Western Blot analyses, Golgi analysis, immunohistochemical analysis to ascertain the potential signaling mechanism(s) that is/are perturbed/altered by overexpression of PLD1 in such diseased states. Result: Chronic PLD1 inhibition ameliorates the synaptic dysfunction and underlying memory deficits in the 3xTg‐AD mouse model by specific action on preserving mushroom spine dendritic spine integrity. Further analysis using Western Blots revealed an underlying mechanism that increases the levels of phosphocofilin in the crude synaptosomal fractions. Conclusion: Using chronic administration of a well‐tolerated halopemide derivative of the specific PLD1 isoform inhibitor in the preclinical mouse models of synaptic dysfunction and memory deficits associated with amyloidogenic effects of Aβ and tau, we demonstrated neuroprotective aspects involving changes in the dendritic spine integrity that contributes to the preservation of memory. Furthermore, we also observed that the mechanism involves actin cytoskeletal dynamics that are modulated via phosphocofilin.